Toward a Single-Valued DMBE Potential Energy Surface for CHNO(3A). 1. Diatomic Fragments - Jimeno, P. (1997)
As a first step toward the construction of a single-valued double many-body expansion potential energy surface for CHNO(3A), we have carried out CASSCF and CASPT2 calculations of six diatomic curves, involving a total of nine electronic states. The ab initio curves have been represented analytically using the extended Hartree−Fock approximate correlation energy model. In all cases, the semiempirical curves have been found to agree well with the available spectroscopic RKR data.